Pengolahan Bahan Pustaka Pascagempa di UPT Perpustakaan Kopertis Wilayah X - Sari, Tika Iman; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2015)
This article aims to describe: (1) how the processing of library materials in the UPT Library Kopertis Wilayah X , (2) what are the obstacles encountered in the processing of library materials in the UPT Library Kopertis Wilayah X (3) what are the efforts made in the processing of library materials in UPT Library Kopertis Wilayah X. the data were collected through direct observation and interviews with librarians in UPT Perpustakaan Kopertis Wilayah X. based on the analysis it can be concluded that the processing of library materials in the Library Kopertis Wilayah X has not been carried out to the maximum. It seen many collections are still scattered on the selves without the appropriate classification number. Constraints of processing library materials after the earthquake of 2009 are: (1) lack of librarians in perticular in the field of Library Science; (2) the lack of infrastructure in the activities of processing library materials. Efforts made in library materials processing activities are: (1) the addition of librarians who are experts in the field of Library Science; (2) provide a special room for library materials processing activities so as not to disturb other library activities; (3) providing complete equipment such as computers, barcode reader, and generator sets in lieu of electricity when a power failure so that library meterials processing activities are not interrupted.Â  Keywords: management, library materials